Influence of Financiers Education on the Quality of Education at Siburbur Elementary School, Tapanuli Regency - Shaleha, Kharida; Panggabean, Dewi Sartika (Cattleya Darmaya Fortuna, 2022)
The results of the study show that there is an influence between the financing of education on the quality of education at SD Siburbur District Tapanuli. This is proven by the acquisition of the value of tcount (6.719)> ttable (2.003) while the test results using simple linear regression indicate that Y = 39.064 + 0.726X, because the regression coefficient is positive (+), so it can be said that education financing has a positive effect on education quality. The value of R Square is 0.446, which means that 44.6% of the quality of education at SD Siburbur District Tapanuli is influenced by education financing, and 55.4% is influenced by other factors such as facilities and infrastructure and the quality of educators.